Human Being – The Object and Subject of Social Education (A Historical Interpretation) - Vaitkevičius, Juozas (Acta Paedagogica Vilnensia, 1993)
The life of a human being and society is not being, but a constantly changing, evolving, unstable process. So the problems of culture and personality development can only be dealt with in the progress of the development of human history. The historical approach allows to reveal the role of an individual within the society and the development of a man himself, his personality. It also better reveals the soundness various theories about the man, his nature, his relations with society, etc., as well as the ways of solving current problems of the human and social development. The article analyses the views of the man and his relationship with society and culture from Antiquity, the Middle Ages, the Renaissance, highlights the major pedagogical ideas of these epochs. While noting that the understanding of man and his essence in the context of nature and culture has been newly elucidated by Kant, Hegel, and Feuerbach, more attention is paid to the analysis of thought of these classical German philosophers. The major insights of intuitive philosophy (Bergson), phenomenological philosophy (Husserl), psychoanalysis (Fromm), pragmatist philosophy (W. James, J. Dewey), and Marxist philosophy are also discussed.